Guide to organic stereochemistry from methane to macromolecules - Buxton, Sheila R (Longman, 1996)
The book takes the reader step-by-step from the structures of simple molecules, such as methane, to the basic shapes of biologically important macromolecules, such as proteins and nucleic acids. The concept of chirality is dealt with by firstly explaining the stereochemistry of compounds with one stereogenic centre, the dealing with compounds having two or more stereogenic centres, before focusing on compounds possessing axes of chirality. The importance of stereochemistry in a wide variety of transformations is discussed. Finally, the book describes the application of stereocontrol in asymmetric synthesis, indicating the use of chiral auxiliaries and chiral catalysts in modern chemistry. The book also includes 460 clear diagrams, questions and answers